2015
DOI: 10.1111/desc.12315
|View full text |Cite
|
Sign up to set email alerts
|

Small on the left, large on the right: numbers orient visual attention onto space in preverbal infants

Abstract: Numbers are represented as ordered magnitudes along a spatially oriented number line. While culture and formal education modulate the direction of this number-space mapping, it is a matter of debate whether its emergence is entirely driven by cultural experience. By registering 8-9-month-old infants' eye movements, this study shows that numerical cues are critical in orienting infants' visual attention towards a peripheral region of space that is congruent with the number's relative position on a left-to-right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
137
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(147 citation statements)
references
References 43 publications
8
137
2
Order By: Relevance
“…In fact, Bulf et al (2016) found that, unlike non-symbolic numerical cues, size cues are not capable to orient spatial attention towards peripheral regions of space in 8-month-old infants. In discussing the discrepancy between the presence of OM for the dimension of size in 12-month-olds and the absence of a size cueing effect in 8-month-olds, Macchi Cassia and colleagues (2016) argued that the phenomenon of mentally spatialize information may emerge first for numerical information and later be extended, possibly by analogy, to other dimensions, such as size.…”
mentioning
confidence: 83%
“…In fact, Bulf et al (2016) found that, unlike non-symbolic numerical cues, size cues are not capable to orient spatial attention towards peripheral regions of space in 8-month-old infants. In discussing the discrepancy between the presence of OM for the dimension of size in 12-month-olds and the absence of a size cueing effect in 8-month-olds, Macchi Cassia and colleagues (2016) argued that the phenomenon of mentally spatialize information may emerge first for numerical information and later be extended, possibly by analogy, to other dimensions, such as size.…”
mentioning
confidence: 83%
“…Xu, Spelke, & Goddard, 2005). Thus, the non-symbolic SNARC, in contrast to the symbolic SNARC, can be tested in children as young as 3 and 4 years (Patro & Haman, 2012) and even in 7-months-old infants (Bulf, de Hevia, & Macchi Cassia, 2016;de Hevia, Girelli, Addabbo, & Macchi Cassia, 2014).…”
Section: Multiple Number-space Associations In Preschool Childrenmentioning
confidence: 99%
“…It cannot, however, be excluded that non-symbolic SNARC-like associationsjust because of this implicit characteristic -are more likely to emerge in tasks based on implicit measures, like speed of spatial responses or attentional shifts to the left or right (cf. Bulf et al, 2016;Ebersbach et al, 2014;Patro & Haman, 2012), which do not require the explicit arrangement of numerosities in space (like the task used in our study). Furthermore, non-symbolic numerosity-based SNA might also partially depend on the acquisition of cardinal principle knowledge.…”
Section: Spatial Arrangement Of Numerositiesmentioning
confidence: 99%
“…Interestingly, there is also a preference for spatially ordered magnitudes early in childhood (de Hevia, Izard, Coubart, Spelke, & Streri, 2014;De Hevia & Spelke, 2010) and this preference is particularly pronounced for a left-to-right arrangement of magnitudes, both in children (Bulf, de Hevia, & Macchi Cassia, 2015;de Hevia, Girelli, Addabbo, & Cassia, 2014) and in newborn chicks (Rugani, Vallortigara, Priftis, & Regolin, 2015; for a critical discussion see . In this issue, Macchi Cassia et al (2016) continue this fascinating line of research by investigating the operational momentum (OM) effect in infants.…”
Section: Development and Impairments Of Number Conceptsmentioning
confidence: 99%